Terahertz transverse-magnetic-polarized waves localized on layered superconductor defect in photonic crystals - Apostolov, S.S.; Iakushev, D.A.; Makarov, N.M.; Shmat’ko, A.A.; Yampol’ski, i V.A. (Радіофізика та електроніка, 2016)
We theoretically study eigenstates of electromagnetic field inside a one-dimensional photonic crystal containing a defect slab of layered superconductor. Basing on the transfer matrix formalism along with the electrodynamics of Josephson plasma, we obtain the dispersion relations describing the THz electromagnetic modes localized on defect. We consider both symmetric and antisymmetric configuration of defect in photonic crystal. The comparison of the dispersion spectra of the localized states for the layered-superconducting defect and the pure insulating defect reveals the features of the studied system.